Real Time Hand Gesture Movements Tracking and Recognizing System - Hartanto, Rudy; Susanto, Adhi; Santosa, Paulus Insap (2014)
Human computer interaction has a long history to become more intuitive. For human being, gesture of different kind is one of the most intuitive and common communication. However, vision-based hand gesture recognition is a challenging problem, which is involved complex computation, due to high degree of freedom in human hand. In this paper, we use hand gesture captured by web-cam instead of mice, for natural and intuitive human-computer interaction. Skin detections method is used to create a segmented hand image and to differentiate with the background. A contours and convex hull algorithm is used to recognize hand area as well as the number of fingertip of hand gesture image to be mapped with button. Moreover, for detection of hand gesture motion, we use Lucas-Kanade pyramidal algorithm. The result shows that this system can operate well so we can interact with computer using our hand gesture instead using a mouse.